Reinforcing Effects of Fentanyl Analogs Found in Illicit Drug Markets - Maitland, Alexander D.; McGriff, Shelby A.; Schindler, Charles W.; Baumann, Michael H. (The Journal of pharmacology and experimental therapeutics, 2024)
Abstract ID 97028 Poster Board 308 The highly potent synthetic opioid fentanyl, and its analogs, continue to drive opioid-related overdoses, burdening public health resources. Although the pharmacology of fentanyl is well characterized, there is little information about the reinforcing effects of newly emerging fentanyl analogs. Here, we compared the effects of fentanyl and clandestine fentanyl analogs (FA) acetylfentanyl, butyrylfentanyl, and cyclopropylfentanyl on drug self-administration behavior in male and female rats. These FAs feature modifications at the carbonyl moiety of the fentanyl scaffold. Sprague-Dawley rats fitted with intravenous jugular catheters were placed in experimental chambers containing two nose poke holes. Active nose poke responses resulted in delivery of a constant volume of drug (0.2 mL) over a period of 2 s on a fixed-ratio 1 schedule, followed by a 20 s timeout. Acquisition doses for the compounds were 0.01 mg/kg/inj for fentanyl and cyclopropylfentanyl, and 0.03 mg/kg/inj for acetylfentanyl and butyrylfentanyl. Following 10 days of acquisition training, dose-effect testing began with three additional doses, each of which were tested for 3 days. Subjects were then returned to the original training dose and underwent 10 days of saline extinction. Acquisition of self-administration for fentanyl and three FAs was achieved by both male and female rats, with significant differences between active versus inactive nose pokes for both sexes by the end of training (p < 0.05). There were no sex differences in active responses for any drugs; however, rates of acquisition varied between sexes across drugs. Fentanyl and tested FAs showed a typical inverted-U dose-effect function during dose-effect testing; acetylfentanyl and butyrylfentanyl were right shifted from fentanyl, while cyclopropylfentanyl produced similar levels of active responding to fentanyl. Maximal response rates were similar among all drugs, with fentanyl and cyclopropylfentanyl showing maximum responding at 0.001 mg/kg/inj, acetylfentanyl at 0.01 mg/kg/inj, and butyrylfentanyl at 0.003 mg/kg/inj. No sex differences in potency or efficacy were detected for any of the drugs tested. Extinction testing revealed no significant differences in responding for any drugs. Our work adds to the converging preclinical evidence that emerging fentanyl analogs display significant abuse liability and may contribute to compulsive use in humans. This work was supported by NIDA DA000523-16.